Le concept de 1’interface intelligent dans la télèdocumentation / The concept of the intelligent interface in online searching - Deschatelets, Gilles (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see pdf